Correction: Non-target mass spectrometry analysis of NDMA precursors in advanced treatment for potable reuse. Issue 3 (17th February 2022) - Roback, Shannon L.; Ferrer, Imma; Thurman, E. Michael; Ishida, Kenneth P.; Plumlee, Megan H.; Poustie, Andrew; Westerhoff, Paul; Hanigan, David
Abstract : Correction for 'Non-target mass spectrometry analysis of NDMA precursors in advanced treatment for potable reuse' by Shannon L. Roback et al., Environ. Sci. : Water Res. Technol., 2018, 4, 1944–1955, DOI: ; 10.1039/C8EW00401C .